DYSTOPOPICAL ASPECTS IN RAY BRADBURY'S "FAHRENHEIT 451" AND IMPACT ON MODERN SOCIETY - Khalilova Shohista Muhammadi kizi (Western European Studies, 2025)
Although Ray Bradbury's "Fahrenheit 451" was written in the 1950s, its dystopian aspects are still very relevant to today's modern society. The book covers a wide range of issues such as the prohibition of knowledge and culture, the negative impact of technology and mass culture on humanity, and the restriction of intellectual freedom. The work shows the dangers associated with totalitarianism and censorship, warning about the loss of personal freedom and social connections. The article covers issues such as the impact of technology and the media on society, the crisis of personal connections, and the loss of free thought in "Fahrenheit 451" . The work raises broad reflections on information manipulation, virtual reality, and the need to preserve free thought today
Keywords: dystopia; totalitarianism; book banning